Treatment outcomes in patients with war related posttraumatic stress disorder in four specialized centres in the Balkans - Priebe, Stefan (Array, 2007)
Relatively little is known about treatment outcomes in patients with war related trauma and the relative impact of different elements of treatment. One of the aims of the STOP study was to benchmark outcomes for different subgroups of patients in specialized treatment centers and to identify other factors associated with a more favorable outcome.